The functional approach, semiotics and professional discourse - Marina Peluso (Training, Language and Culture, 2021)
Michael Halliday, the founder of Systemic Functional Linguistics, was the key figure in linguistics to focus on the meaning of language as communication rather than just its structural form. He saw language as meaning and as a semiotic representation of values, attitudes and behaviours and in doing so introduced a vital area of academic study of languages. This paper explores the origins of Systemic Functional Linguistics and semiology, as well as the relationship between them, especially in applied professional discourse, both spoken and written. It analyses the use of Systemic Functional Linguistics in three case studies based on communication, semantics and non-verbal communication, and examines the implications for foreign language learning and teaching. The objective of the paper is to analyse Systemic Functional Linguistics (SFL) and to show how it is exploited in newer communication approaches of Semiotics and UXD in intercultural business communication in English. The methodology is based on secondary research and focuses on three case studies, each presenting a new dimension of professional communication discourse. The first is the introduction of Globish, a simplified business vocabulary and grammar based on the requirements of international business negotiation. The second is the use of semiotics – signs that convey meaning and register. The third is the use of non-verbal communication based on the experiments of Albert Mehrabian. The results show that in a globalising economy Halliday’s Systemic Functional Linguistics is an essential tool in managing international intercultural communication and professional discourse, but that ways of using discourse to convey meaning need to be considered.